EFEKTIFITAS SUSCATIN (KURSUS CALON PENGANTIN) DALAM MEMBENTUK KELUARGA BAHAGIA (Studi Kuantitatif di Kecamatan Sumbersuko, Lumajang) (Jurusan Bimbingan dan Konseling Islam, 2016)
This study examines about the process of SUSCATIN (the course of the bride and bridegroom candidate or pre wedding counseling) and the effectiveness of SUSCATIN which was done by KUA Kecamatan Sumbersuko, Lumajang to create a happy family. This study used quantitative approach by using survey method which is research method to collect data from the specific natural place but the researcher did a treatment in collecting the data. In this study, the researcher only did one test because the part of KUA Kecamatan Sumbersuko, Lumajang had done SUSCATIN to the object that will be examined. The result of this research which had been done by KUA Kecamatan Sumbersuko, Lumajang is effective in creating a happy family